Screening of Lactiplantibacillus plantarum 67 with Strong Adhesion to Caco-2 Cells and the Effects of Protective Agents on Its Adhesion Ability during Vacuum Freeze Drying - Dawei Chen; Congcong Guo; Chenyu Ren; Zihan Xia; Haiyan Xu; Hengxian Qu; Yunchao Wa; Chengran Guan; Chenchen Zhang; Jianya Qian; Ruixia Gu (Foods, 2023)
Adhesion to the intestinal tract provides the foundation for Lactobacillus to exert its benefits. Vacuum freeze-drying (VFD) is currently one of the main processing methods for Lactobacillus products. Therefore, the effects of VFD on the adhesion and survival of Lactiplantibacillus plantarum 67 were investigated in this study. The results show that L. plantarum 67 exhibits remarkable tolerance following successive exposure to simulated saliva, gastric juice and intestinal juice, and also has a strong adhesion ability to Caco-2 cells. The adhesion and survival rates of L. plantarum 67 significantly decreased after VFD in phosphate-buffered saline (PBS), whereas they significantly increased in protective agents (PAs) (p < 0.05). Scanning electron microscope observations show that L. plantarum 67 aggregated more to Caco-2 cells in PAs than in PBS, and its shape and size were protected. Proteomics detection findings indicated that differentially expressed proteins (DEPs) related to adhesins and vitality and their pathways in L. plantarum 67 were significantly affected by VFD (p < 0.05). However, the expression of DEPs (such as cold shock protein, cell surface protein, adherence protein, chitin-binding domain and extracellular transglycosylase, membrane-bound protein) was improved by PAs. Compared with PBS, the PAs significantly adjusted the phosphotransferase system and amino sugar and nucleotide sugar metabolism pathways (p < 0.05). VFD decreased the adhesion and vitality of L. plantarum 67, while the PAs could exert protective effects by regulating proteins and pathways related to adhesion and vitality.